2008
DOI: 10.1021/ie061655x
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of Cr(VI) Immobilization Using Nanoscale Zerovalent Iron (nZVI):  A Study with High-Resolution X-Ray Photoelectron Spectroscopy (HR-XPS)

Abstract: Remediation of chromium-contaminated sites presents both technological and economic challenges as conventional methods are often too expensive in removing chromium in the soil matrix such as chromium ore process residue (COPR). In this work, reduction and precipitation of hexavalent chromium [Cr(VI)] by nanoscale zerovalent iron (nZVI) are evaluated. Cr(VI) is rapidly reduced and immobilized on the iron nanoparticle surface. In the pH range of 4 to 8, the nZVI has a chromium removal capacity ranging from 180 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(190 citation statements)
references
References 39 publications
13
174
1
2
Order By: Relevance
“…Four Cr photo-electron peaks were observed for the untreated COPR sample where two 2p 3/2 peaks were centered at 577.3 and 579.6 eV and two 2p 1/2 peaks at 586.9 and 589.0 eV. The binding energies of the Cr 2p 3/2 peak at 577.3 eV and the Cr 2p 1/2 peak at 586.9 eV were consistent with reported values for Cr 2 O 3 , CrOOH, and Cr(OH) 3 which was in the energy range 576.2-577.5 eV for 2p 3/2 and 586.7-587.0 eV for 2p 1/2 , respectively [38][39][40]. Furthermore, the magnitude of the spin-orbit splitting (SOS) between these two peaks was 9.6 eV, which was the characteristic of Cr(III) with reported SOS of 9.7-9.9 eV [41].…”
Section: Analysis Of Cr(vi) Reduction By Xpssupporting
confidence: 89%
See 1 more Smart Citation
“…Four Cr photo-electron peaks were observed for the untreated COPR sample where two 2p 3/2 peaks were centered at 577.3 and 579.6 eV and two 2p 1/2 peaks at 586.9 and 589.0 eV. The binding energies of the Cr 2p 3/2 peak at 577.3 eV and the Cr 2p 1/2 peak at 586.9 eV were consistent with reported values for Cr 2 O 3 , CrOOH, and Cr(OH) 3 which was in the energy range 576.2-577.5 eV for 2p 3/2 and 586.7-587.0 eV for 2p 1/2 , respectively [38][39][40]. Furthermore, the magnitude of the spin-orbit splitting (SOS) between these two peaks was 9.6 eV, which was the characteristic of Cr(III) with reported SOS of 9.7-9.9 eV [41].…”
Section: Analysis Of Cr(vi) Reduction By Xpssupporting
confidence: 89%
“…The binding energy of the 2p 3/2 peak at 579.6 eV was comparable to reported values for Cr(VI) which range from 579.0 to 579.8 eV [42]. The SOS for Cr(VI) was 9.4 eV, in agreement with the reported range 9.2-9.4 eV [39,43].…”
Section: Analysis Of Cr(vi) Reduction By Xpssupporting
confidence: 89%
“…In addition, the effectiveness of metal removal can be determined using applied SnZVI into aqueous solution of Cr(VI). Rise in the solution pH may be contributed to the release of OH -ions due to redox reaction below (Li et al, 2008): Higher efficiency of SnZVI compared to CnZVI and ZVI could be explained by the higher reduction of Cr(VI) to Cr(III) at high solution pH. This finding was confirmed by the EDS spectra showing a higher peak and Cr concentration at a 0.2% application rate of SnZVI to Cr(VI) aqueous solution (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Zerovalent iron has a high redox potential to transfer Cr(VI) to Cr(III) in aqueous solutions (Lee et al, 2003;Yang et al, 2007). Numerous studies have been reported on the use of ZVIs for removing Cr(VI) in aqueous solutions (Fendorf and Li, 1996;Ponder et al, 2000;Yang et al, 2006;Yang et al, 2007;Li et al, 2008). The mechanism of Cr(VI) removal from aqueous solutions by nZVIs consists of the reduction, complexation, adsorption, precipitation or coprecipitation (Yang et al, 2007).…”
Section: Open Access Research Articlementioning
confidence: 99%
“…On the basis of solution chemistry and X-ray photoelectron spectroscopy data, Li et al (2008) determined the average value of x, and it was found to be approximately 0.667. This Cr-Fe oxyhydroxide shell is stable and serves as a sink for Cr(VI).…”
Section: Resultsmentioning
confidence: 99%